PERENCANAAN PROGRAM PELATIHAN DALAM RANGKA MENDUKUNG PRODUKTIVITAS KARYAWAN PADA PT LANGGENG JAYA PLASTINDO - Robi'atul Adawiyah; Maulidyah Amalina Rizqi (MANAJEMEN DEWANTARA, 2026)
This study aims to determine the factors causing employee training programs that are not implemented according to plan and analyze the impact of training programs that are not implemented at PT Langgeng Jaya Plastindo. This study uses a sampling technique with a descriptive qualitative method and data collection using interviews. Informant data collection uses a purposive sampling technique. The results of the interview obtained that the employee training program at PT Langgeng Jaya Plastindo has not been in accordance with the plans made due to several factors such as managerial and operational constraints, the impact of not implementing training causes difficulties for employees to operate machines, the results of the data also show an increase in productivity in employees who have participated in the training program